The variability of the BRITE-est Wolf–Rayet binary, γ2 Velorum–I. Photometric and spectroscopic evidence for colliding winds. Issue 3 (13th July 2017) - Richardson, Noel D.; Russell, Christopher M. P.; St-Jean, Lucas; Moffat, Anthony F. J.; St-Louis, Nicole; Shenar, Tomer; Pablo, Herbert; Hill, Grant M.; Ramiaramanantsoa, Tahina; Corcoran, Michael; Hamuguchi, Kenji; Eversberg, Thomas; et al.
Abstract: We report on the first multi-colour precision light curve of the bright Wolf–Rayet binary γ 2 Velorum, obtained over six months with the nanosatellites in the BRITE-Constellation fleet. In parallel, we obtained 488 high-resolution optical spectra of the system. In this first report on the data sets, we revise the spectroscopic orbit and report on the bulk properties of the colliding winds. We find a dependence of both the light curve and excess emission properties that scales with the inverse of the binary separation. When analysing the spectroscopic properties in combination with the photometry, we find that the phase dependence is caused only by excess emission in the lines, and not from a changing continuum. We also detect a narrow, high-velocity absorption component from the He i λ5876 transition, which appears twice in the orbit. We calculate smoothed-particle hydrodynamical simulations of the colliding winds and can accurately associate the absorption from He i to the leading and trailing arms of the wind shock cone passing tangentially through our line of sight. The simulations also explain the general strength and kinematics of the emission excess observed in wind lines such as C iii λ5696 of the system. These results represent the first in a series of investigations into the winds and properties of γ 2 Velorum through multi-technique and multi-wavelength observational campaigns.